DIE SPRICHWÖRTLICHE REDENSARTEN - Huseynzade Khoshgadam (World Science, 2018)
In this article we are talking about the phraseology of proverbs in German and Azerbaijani. What are proverbs? - These are a set of complete phrases created by the people, tested by experiments and time, briefly and clearly expressed in the public. "Love does not get old"(Alte Liebe rostet nicht.), "The Word of Men is the Law"- «Ein Mann, ein Wort». That concrete and abstract proverbs retain the meaning and essence of the sentence as distinct from riddles and idiomatic expressions.They correspond to the phraseological compounds of V. Vinogradov's classification, are an integral part of the language and enrich the vocabulary of the German language. This classification is based on a functional principle and therefore they can be applied both in style and in lexicology. This article deals with word combinations, phraseological units and compounds, idiomatic expressions, winged phrases and proverbs.